Combating the threat of pandemic influenza : (John Wiley & Sons, 2007)
Combating the Threat of Pandemic Influenza: Drug Discovery Approaches consolidates the latest information on diverse approaches into one comprehensive resource. It is an invaluable, hands-on reference for researchers in medicinal chemistry, pharmaceutical chemistry, drug discovery, biochemistry, virology, microbiology, and public health.